Interspeech 2021 2021
DOI: 10.21437/interspeech.2021-336
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Different Levels of Speech Information from EEG Using an LSTM-Based Model

Abstract: Decoding the speech signal that a person is listening to from the human brain via electroencephalography (EEG) can help us understand how our auditory system works. Linear models have been used to reconstruct the EEG from speech or vice versa. Recently, Artificial Neural Networks (ANNs) such as Convolutional Neural Network (CNN) and Long Short-Term Memory (LSTM) based architectures have outperformed linear models in modeling the relation between EEG and speech. Before attempting to use these models in real-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Throughout the recording session, participants were given short breaks. A subset of this dataset was also used in Accou et al 11,12 , Monesi et al 9,10 and Bollens et al 24 , and is available for the Auditory EEG decoding challenge (https:// exporl. github.…”
Section: Cnnmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the recording session, participants were given short breaks. A subset of this dataset was also used in Accou et al 11,12 , Monesi et al 9,10 and Bollens et al 24 , and is available for the Auditory EEG decoding challenge (https:// exporl. github.…”
Section: Cnnmentioning
confidence: 99%
“…by decoding speech from brain signals [5][6][7] , or by translating both brain signal and speech features to a similar representation 8,9 . Neural tracking in EEG has been found for multiple acoustic representations of speech, such as the spectrogram 7,10 or envelope representations 5,6,11,12 . Additionally, neural tracking has been shown for higher order representations such as semantic dissimilarity, cohort entropy, word surprisal, and phoneme surprisal [13][14][15][16] .…”
mentioning
confidence: 99%
“…A subset of this dataset was also used in Accou et al 5,6 , Monesi et al 4,20 and Bollens et al 21 This dataset contains approximately 188 hours of EEG recordings (on average 1 hour and 46 minutes per subject) in total.…”
Section: Datasetmentioning
confidence: 99%
“…Recent research has focused on detecting neural tracking of speech features in EEG to understand how speech is procesed by the brain [1][2][3] . Neural tracking has been found for multiple acoustic representations of speech, such as the spectrogram 2,4 or envelope representations 1,3,5,6 . Additionally, neural tracking has been shown for higher order representations such as semantic dissimilarity, cohort entropy, word surprisal, and phoneme surprisal [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm can also be solved in a non-linear fashion with neural networks (e.g. Accou et al, 2021;Monesi et al, 2021;Bollens et al, 2022). Accou et al (2021) showed that the accuracy of a neural network solving a match-mismatch task could be used to estimate the speech reception threshold.…”
Section: Other Methods To Extract Neural Trackingmentioning
confidence: 99%